2022
DOI: 10.1039/d2cp03401h
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the synergetic interaction between amino and carbonyl functional groups and their effect on the electronic and optical properties of carbon dots

Abstract: Nitrogen and oxygen-based functionalized Carbon dots' (CDs) surfaces have attracted significant attention owing to their ability to tailor CDs' optical and electronic properties. However, the complex synthesis process and structure...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 57 publications
(102 reference statements)
1
5
0
Order By: Relevance
“…The peak at 1628 cm –1 indicated that the C=O/C=C functional group involved in the conjugated double bond of carbon with the C-O/C-N at 1454 and 1363 cm –1 resulted in the fluorescence of CDs after lightening by the UV beam. 33 , 34 As reported in our previous work, these typical CDs plausibly consist of various C–N configurations, including Pyridinic-N, Pyrrolic-N, Graphitic-N, and Amino-N, on their surfaces. 35 Therefore, it is highly plausible that the as-prepared CDs are N-doped CDs rather than pristine CDs.…”
Section: Resultssupporting
confidence: 61%
“…The peak at 1628 cm –1 indicated that the C=O/C=C functional group involved in the conjugated double bond of carbon with the C-O/C-N at 1454 and 1363 cm –1 resulted in the fluorescence of CDs after lightening by the UV beam. 33 , 34 As reported in our previous work, these typical CDs plausibly consist of various C–N configurations, including Pyridinic-N, Pyrrolic-N, Graphitic-N, and Amino-N, on their surfaces. 35 Therefore, it is highly plausible that the as-prepared CDs are N-doped CDs rather than pristine CDs.…”
Section: Resultssupporting
confidence: 61%
“…This result is based on a few studies using urea as a carbonyl and amino group precursor. Santika et al showed that carbonyl and amino groups provide the absorbance peak shifting farther than the other doping, which only had one of the groups . The carbonyl group was related to shifting under the empty molecular orbital, while the amino group donated their electron to the carbonyl system; therefore, it will meaningfully shift the absorbance peak to the farther wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have turned to carbon dots as potential alternatives to address this issue. Carbon dots (CDs), the newly discovered RTP materials, have recently gained much attention due to their facile preparation, low cost, good photostability, and low toxicity. Various synthesis methods have been developed, including top-down and bottom-up methods, for CDs due to their outstanding properties. The microwave method has gained significant popularity in synthesizing and modifying CDs due to its capability to uniformly and rapidly penetrate and heat samples. This feature enables shorter synthesis times, facilitating expedited advancements in material development.…”
Section: Introductionmentioning
confidence: 99%